2017
DOI: 10.1186/s12913-017-2325-x
|View full text |Cite
|
Sign up to set email alerts
|

Introducing onsite antenatal syphilis screening in Burkina Faso: implementation and evaluation of a feasibility intervention tailored to a local context

Abstract: BackgroundAlthough the advantages of introducing point of care testing for syphilis in antenatal care (ANC) are well documented, there is little evidence on how to address structural issues within health systems. A better understanding of how these interventions work in a range of settings and contexts is needed in order to overcome bottlenecks at health system level. To better understand the relationships between implementation and context we developed and implemented an intervention focused on integrating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 35 publications
(22 reference statements)
1
40
0
2
Order By: Relevance
“…Barriers for the successful implementation of same-day screening and treatment for syphilis at first ANC visit exist at system-, facility- provider- and patient-levels. Findings are similar than the reported in other studies [ 23 25 ]. System-level barriers include poor geographical and functional accessibility, lack of human resources and supplies, and established norms that need to be changed in order to implement the new practice, as well as the broader economic situation in these countries.…”
Section: Discussionsupporting
confidence: 91%
“…Barriers for the successful implementation of same-day screening and treatment for syphilis at first ANC visit exist at system-, facility- provider- and patient-levels. Findings are similar than the reported in other studies [ 23 25 ]. System-level barriers include poor geographical and functional accessibility, lack of human resources and supplies, and established norms that need to be changed in order to implement the new practice, as well as the broader economic situation in these countries.…”
Section: Discussionsupporting
confidence: 91%
“…Bee et al [ 71 ] UK NPT Cognitive behavioural therapy by phone Systematic reviews [ 227 , 228 ] Feasibility study Qualitative Prospective Yes No No 38. Bocum et al [ 72 ] Burkina Faso NPM Antenatal syphilis screening Feasibility study Qualitative Retrospective Yes No Yes 39. Bouamrane and Mair [ 73 ] UK NPT Surgical assessment (online) Systematic review [ 168 ] Yes Process evaluation Qualitative Prospective Yes No N/A 40.…”
Section: Resultsmentioning
confidence: 99%
“…Here, a Norwegian team led by Wilhelmsen et al [ 145 ] showed how problems of participation and action—and especially the interactional workability—of a service providing internet-based cognitive behavioural therapy led to ambivalence on the part of general practitioners about its use, to low levels of follow-up and to doctors reverting to ‘standard treatment’ [ 145 ]. Less numerous ( n = 11, 10.1%, were studies of the implementation of screening and surveillance tools [ 38 42 , 53 , 64 , 65 , 72 , 77 , 113 , 129 , 132 , 139 , 144 ]). In a feasibility study, Ahmed et al [ 64 ] showed that integrating a family history questionnaire about common genetic diseases into the workflow of primary care was unlikely without significant changes to the pattern of GP-patient interactions, and these were unlikely to be supported by clinicians.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly worrying is the lack of knowledge regarding the rapid syphilis test, recommended by the WHO to improve access to syphilis diagnosis. There is evidence of the cost‐effectiveness of these tests for the treatment of syphilis during pregnancy and reports of high acceptance among professionals and users . The Brazilian MoH established the implementation of RST in PNC in 2011, which may explain the lower familiarity of professionals with these tests, given its more recent deployment.…”
Section: Discussionmentioning
confidence: 99%